Aplikasi Sistem Penujang Keputusan Penilaian Karyawan Terbaik dengan Metode Multi Attributive Border Approxmation Area Comparsion (MABAC) (Studi Kasus : PT. Wirasandi) - Shandi Noris; Edison Putra Zebua (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
Employee performance evaluation is an important process in improving company productivity and work quality. However, the employee evaluation process at PT. Wirasandi was previously conducted manually, which could lead to subjectivity and inaccuracies in decision making. Therefore, this study aims to design and develop a Decision Support System (DSS) application for selecting the best employees using the Multi-Attributive Border Approximation Area Comparison (MABAC) method. The system is developed as a web-based application using PHP as the programming language and MySQL as the database management system. The MABAC method is applied to assist decision making by considering multiple evaluation criteria that have been determined. The stages of the MABAC method include constructing the decision matrix, normalization, weighting, determining the border approximation area, and calculating preference values to rank employees. The results of system testing using White Box and Black Box testing methods indicate that all system functions operate according to the specified requirements. The developed application is able to generate employee rankings objectively, accurately, and systematically. Therefore, this decision support system is expected to assist the management of PT. Wirasandi in determining the best employees effectively and efficiently.